PERFORMANCE CHARACTERISTICS OF FUNGAL DEGRADED RICE BRAN AND PALM KERNEL CAKE SUBSTITUTED IN Clarias gariepinus FEEDS (2014)
Fish farming enterprise has increased in recent times due to public demand for fish protein. However, rising costs of fish feed ingredients have greatly reduced the profit margin of local fish farmers. Cheap, readily available and locally sourced ingredients may be better substitutes to the costly fish feeds. The aim of this study was to evaluate the performance of fermented Palm Kernel Cake (PKC) and Rice Bran (RB) as substitutes in the diet of Clarias gariepinus. Fungi were isolated from Unfermented PKC (UPKC), RB (URB) and from Naturally-Fermented PKC (NFPKC) and RB (NFRB) ligno-cellulosic substrates using Potato Dextrose Agar (PDA). Isolates were identified and screened for enzyme production (amylase and cellulase) using standard methods. They were then subjected to physico-chemical (pH, temperature, incubation period, carbon and nitrogen sources) analysis to obtain optimal conditions for enzyme production. Proximate analysis of fungi-fermented samples was carried out to select the starters used in degrading the ligno-cellulosic substrates. Starters that gave the highest protein contents were selected. Starter-Degraded PKC (SDPKC) and RB (SDRB) were analysed for proximate and mineral compositions, amino acid profile, anti-nutrition factors, vitamins and heavy metals. The degraded and undegraded ligno-cellulosic bulks were substituted in the diets of fingerling and compared with a standard fish feed as control for three months. Fish performance characteristics [(Mean Weight Gain (MWG), Specific Growth Rate (SGR)] and Feed Conversion Ratio (FCR)) were evaluated. Data were analysed using ANOVA at p=0.05. Ten fungi isolates obtained were Aspergillus fumigatus, Aspergillus niger, Aspergillus clavatus, Aspergillus tamarii, Aspergillus terreus, Aspergillus versicolor, Rhizopus stolonifer, Rhizopus oryzae, Rhizopus sp. and Trichoderma sp. Highest amylase (63.2units/mg) at pH 6.0, 50.0oC, Vmax 3.9 (UI/mL) and Km 1.3 (g/mL) was produced by Aspergillus niger which grew best on wheat bran (8.0 mg/g) as carbon source and ammonium nitrate (4.6 mg/g) as nitrogen source. Highest cellulase (3.1Units/mg) at pH 8.0, 20.0oC, Vmax 0.9 (UI/mL) and Km 0.8(g/mL) was produced by Rhizopus oryzae which grew best on RB (7.3 mg/g) as carbon source and potassium nitrate (1.6 mg/g) as nitrogen source. Selected starters, Aspergillus clavatus and Aspergillus tamarii, gave protein contents of 6.5% and 17.9%. Protein contents of NFPKC, NFRB, UPKC and URB were 5.7, 22.0, 5.2 and 16.0% respectively. Highest zinc composition (520.0µg/g) was recorded in SDPKC and SDRB with reduction in amino acid profile (16.7 – 0.03µg/g). Fermentation decreased oxalate (24.1-18.2 µg/g) among the anti-nutritional factors and had no effect on the vitamin contents, while no heavy metal was detected in the feeds. The MWG of fish fed with URB and UPKC ranged from 18.9g - 35.8g and that of SDRB and SDPKC ranged from 12.8 - 43.3g while that of the control feed was 31.5g. Fish fed SDPKC gave the highest SGR of 1.3g/day and the lowest FCR of 1.4. Significant difference in SGR was observed between fish fed with SDPKC and UPKC. Fungi degraded palm kernel cake and rice bran supported the growth of Clarias gariepinus better than the control feed and could be good sources of fish feed components.